2016
DOI: 10.3386/w22796
|View full text |Cite
|
Sign up to set email alerts
|

The Mortality and Medical Costs of Air Pollution: Evidence from Changes in Wind Direction

Abstract: , and the WCERE for helpful comments. Dominik Mockus and Eric Zou provided excellent research assistance. We thank Jean Roth for assistance with the Medicare data and Daniel Feenberg and Mohan Ramanujan for system administration. Research reported in this publication was supported by the National Institute on Aging of the National Institutes of Health under Award Number R01AG053350. The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
215
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(239 citation statements)
references
References 47 publications
(70 reference statements)
19
215
3
1
Order By: Relevance
“…These long-run health problems can manifest themselves in the short run if high levels of pollution trigger conditions resulting from previously accumulated exposure. Infant (Chay and Greenstone, 2003) and elderly morbidity resulting from air pollution (Deryugina et al, 2016) can require working adults to miss work to care for them (Aragon et al, 2016;Hanna and Oliva, 2015). Long-term exposure can also reduce life expectancy (Chen et al, 2013a) which can result in experienced workers being replaced by new, inexperienced ones.…”
Section: Pollution and Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…These long-run health problems can manifest themselves in the short run if high levels of pollution trigger conditions resulting from previously accumulated exposure. Infant (Chay and Greenstone, 2003) and elderly morbidity resulting from air pollution (Deryugina et al, 2016) can require working adults to miss work to care for them (Aragon et al, 2016;Hanna and Oliva, 2015). Long-term exposure can also reduce life expectancy (Chen et al, 2013a) which can result in experienced workers being replaced by new, inexperienced ones.…”
Section: Pollution and Productivitymentioning
confidence: 99%
“…To ensure exogeneity, we condition on the wind blowing from the nearby to the focal city (when the wind blows toward the nearby city its pollution measure is not exogenous because greater focal city output would increase the nearby city's air pollution level) and show that the timing of this is random. Wind direction has been used as an instrument for air pollution in a few studies (Luechinger, 2009;Schlenker and Walker, 2011;Deryugina et al, 2016). Identification requires that the instrument be sufficiently correlated with the endogenous regressor and uncorrelated with any unobserved determinant of the dependent variable.…”
Section: Air Quality Of Nearby City As Instrumentmentioning
confidence: 99%
“…Evidence for these regulations comes mainly from associative studies that have consistently demonstrated a relationship between PM 2.5 and increased morbidity and mortality. Deryugina et al (2016) found an increase in daily PM 2.5 three-day mortality. Thus, they guess that each 1 µg/m 3 increase in PM 2.5 increases the three-day emergency visits by 2.3 per million beneficiaries.…”
Section: Variables (Axes F1 Et F2: 9908 %)mentioning
confidence: 89%
“…Yet, little empirical evidence exists on the impacts of car exhaust on health outcomes. Although it is well established that air pollution has negative impacts on population health (Chay and Greenstone, 2003a,b;Currie and Neidell, 2005;Chen et al, 2013;Deschenes et al, 2017;Deryugina et al, 2019), the existing quasi-experimental evidence is largely based on measures of overall air pollution without identifying the contribution of car pollution. Two pioneering papers have studied the health impacts of car pollution on disadvantaged infants-those born to mothers residing next to highway toll stations and those sick enough to die in response to weekly traffic variation (Currie and Walker, 2011;Knittel et al, 2016)-but these estimates might not be generalizable.…”
Section: Introductionmentioning
confidence: 99%